Placenta wit : mother stories, rituals, and research - Jordan, Nané (Demeter Press, 2017)
Placenta Wit is an interdisciplinary anthology of stories, rituals, and research that explores mothers' contemporary and traditional uses of the human afterbirth. Authors inspire, provoke and highlight diverse understandings of the placenta and its role in mothers' creative life-giving. Through medicalization of childbirth, many North American mothers do not have access to their babies' placentas, nor would many think to. Placentas are often considered to be medical property, and/ or viewed as the refuse of birth. Yet there is now greater understanding of motherand baby-centred birth care, in.